The Modigliani-Miller theorems: a cornerstone of finance - Pagano, Marco (PSL Quarterly Review, 2012)
The Modigliani-Miller (MM) theorems are a cornerstone of finance for two reasons. The first is substantive and it stems from their nature of "irrelevance propositions": by providing a crystal-clear benchmark case where capital structure and dividend policy do not affect firm value, by implication these propositions help us understand when these decisions may affect the value of firms, and why. Indeed, the entire subsequent development of corporate finance can be described essentially as exploring the consequences of relaxing the MM assumptions. The second reason for the seminal importance of MM is methodological, by relying on an arbitrage argument, they set a precedent not only within the realm of corporate finance but also (and even more importantly) within that of asset pricing. JEL Codes: G00